2008
DOI: 10.1063/1.3000631
|View full text |Cite
|
Sign up to set email alerts
|

Particle size effect on strength, failure, and shock behavior in polytetrafluoroethylene-Al-W granular composite materials

Abstract: The variation of metallic particle size and sample porosity significantly alters the dynamic mechanical properties of high density granular composites processed using a cold isostatically pressed mixture of polytetrafluoroethylene (PTFE), aluminum (Al) and tungsten (W) powders. Quasi-static and dynamic experiments are performed with identical constituent mass fractions with variations in the size of the W particles and pressing conditions. The relatively weak polymer matrix allows the strength and fracture mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(71 citation statements)
references
References 27 publications
2
66
0
Order By: Relevance
“…This behavior is similar to observations in the PTFE-Al-W mixtures and in the experiments with the Al-W powder mixture. 11,12,[16][17][18] The global shear localized zones and the subsequent cracks developed at an approximate 45 degree angle but was kinked by the rigid W particles resulting in the initial shear band forming in a range of angles from 36 to 50 degrees (see Fig. 9).…”
Section: Numerical Modeling and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This behavior is similar to observations in the PTFE-Al-W mixtures and in the experiments with the Al-W powder mixture. 11,12,[16][17][18] The global shear localized zones and the subsequent cracks developed at an approximate 45 degree angle but was kinked by the rigid W particles resulting in the initial shear band forming in a range of angles from 36 to 50 degrees (see Fig. 9).…”
Section: Numerical Modeling and Discussionmentioning
confidence: 99%
“…A similar effect of rigid and heavy W particles is instrumental also in the shock loading of corresponding mixtures allowing tailored redistribution of internal energy between components. 11,12 G. The role of the constitutive behavior of Al…”
Section: The Relationship Between Sample Strength and Porosity In mentioning
confidence: 99%
See 2 more Smart Citations
“…These studies have shown that particle size [15,19,21,22], shape [23] and concentration [24] and properties of the constituents can affect mechanical properties. In Al 2 O 3 particle-filled epoxy (Epon 828/Z), increasing the particle concentration and decreasing the particle size is found to increase the stress corresponding to 4% plastic strain [25].…”
mentioning
confidence: 99%